Implementing Character Education in Early Childhood: A Case Study of an Islamic Preschool in Indonesia - Salma, Sitti; Ampa, Andi Tendri; Bahri, Aliem (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study aims to investigate the implementation of character education at the Early Childhood Education (PAUD) center Al Manshurin in Kendari City. Employing a qualitative field research methodology, the research observed phenomena within the natural school context. Data were collected through observation, interviews, and documentation involving two key informants: one Group B teacher and the principal. The collected data were analyzed using a qualitative approach encompassing data reduction, data presentation, and conclusion drawing/verification. The results indicate that the implementation, as carried out by the Group B teacher from November to December 2023, was effective. Character education was successfully integrated into daily activities, focusing on cultivating six core noble traits: discipline, honesty, trustworthiness, independence, patience, and mutual respect. The practical implication of this research is that it provides a replicable model for embedding specific character values through consistent routine practices in early childhood settings. The novelty and contribution of this work lie in its focused, empirical examination of a localized Indonesian PAUD context, detailing the operationalization of a distinct set of character values. It contributes to the broader discourse on character education by demonstrating a practical framework for its actualization in early childhood education, offering insights for educators and policymakers aiming to foster moral development from an early age.